2019
DOI: 10.1002/jcb.29152
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of pluripotent long noncoding RNA ES3 in HER2‐positive breast cancer

Abstract: Breast cancer is the second most common cancer and estimates to be responsible for 20% of all cancer patients. Breast cancer has several subtypes including luminal A, luminal B, normal breast‐like, basal‐like, and human epidermal growth factor receptor 2 (HER2)‐enriched. HER2‐positive breast cancer cells have higher HER2 expression than other breast cancer subtypes. This subtype is the most aggressive breast cancer subtype and has more ability to metastasis than other breast cancer subtypes. HER2 is a growth‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…[ 8 9 10 ] Increasing studies have found that lncRNAs exist abnormal expression and related to prognosis in BC. [ 11 12 13 ] However, there are few studies on the prognostic value of uniting biomarkers and other clinical indicators.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 9 10 ] Increasing studies have found that lncRNAs exist abnormal expression and related to prognosis in BC. [ 11 12 13 ] However, there are few studies on the prognostic value of uniting biomarkers and other clinical indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also indicated that some lncRNAs play a central role in both embryonic stem cells and cancer cells [4]. For instance, lncRNA MIAT, ES3, and ES1 not only contribute to maintaining pluripotency in embryonic stem cells, but they also play a crucial role in tumorigenesis, tumor progression, and metastasis [5][6][7][8]. PNKY is also a long non-coding RNA that regulates the pluripotency and differentiation of embryonic and postnatal neural stem cells (NSCs).…”
Section: Introductionmentioning
confidence: 99%